2
$\begingroup$

Suppose that

$Z(t)=e^{-\int_0^t \theta'(s)dW(s)-\frac{1}{2}\int_0^t ||\theta(s)||^2ds}$

with $\theta()=\sigma^{-1}()[b()-r()]$, $\sigma()>0$ and invertable and $W()$ a Wiener process

There is also a process $V^{w,h}$ for describing the wealth of an investor such that

$\frac{V^{w,h}(t)}{B(t)}=w+\int_0^t\frac{h'(s)}{B(s)}\sigma(s)[dW(s)+\theta(s)ds]$

with $0\le t\le T$, $w$ being the initial wealth and $A(w)=\{h()/V^{w,h}()\ge 0\}$ almost surely.

Can you help me show that $\frac{V^{w,h}(t)}{B(t)}Z(t)=w+\int_0^t\frac{Z(t)}{B(s)}[V^{w,h}(s)(\theta(s))'-h'(s)\sigma(s)]dW(s)$ ?

I am new to stochastic calculus and i don't know how to correctly apply Ito's Lemma

$\endgroup$
3
$\begingroup$

Hints:

Use Ito theorem for $\ln Z_t$ to get:

$$dZ_t = -\theta_t Z_t dW_t $$

Then use the product rule to compute $d(U_tZ_t)$. I introduced $U_t:=V_t B_t^{-1}$ to keep things cleaner.

$$dU_t = h'_t B_t^{-1}\sigma_t dW_t + h'_t B_t^{-1}\sigma_t \theta_t dt $$

$$ dU_t\cdot dZ_t = -h'_t B_t^{-1}\sigma_t \theta_t Z_t dt $$

$$ d(U_tZ_t) = U_tdZ_t + Z_tdU_t +dU_t\cdot dZ_t$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.